Effect of Anisaldehyde as Corrosion Inhibitor for Aluminium in Sulphuric Acid Solution - Husaini, Musa (Journal of Science and Technology, 2020)
The inhibition effect of anisaldehyde on the corrosion of aluminium in sulphuric acid was investigated by weight loss method and characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) analyses. The effect of different inhibitor concentrations was studied at varying temperature (308, 313 and 318 K). It was found that the percentage of inhibition efficiency (% I.E.) increases with increase of inhibitor concentration and decreases with increase in temperature. The values of activation energy and half-life were found to be higher in inhibited acid solution compared to uninhibited acid solution, while that for the rate constant reduced from uninhibited to inhibited acid solution. The negative values of Gibbs free energy of adsorption confirmed the spontaneity of the process. Other thermodynamic parameters such as enthalpy and entropy were also evaluated and discussed. The investigation of adsorption isotherm model indicates that the inhibitor fitted to Langmuir isotherm model. Result of SEM analysis shows how the inhibitor reduced the acid attack on the aluminium surface, and FTIR analysis result of the corrosion product proves the formation of thin layer of inhibitor molecules on aluminium surface.